2013
DOI: 10.1002/trtr.1203
|View full text |Cite
|
Sign up to set email alerts
|

Let's Bring Back the Magic of Song for Teaching Reading

Abstract: Based on a first grade teacher's search for approaches to promote successful reading acquisition in her first grade classroom, the authors present a curricular engagement in which the teacher explored using music, specifically singing songs, as a fun and motivating way to accelerate reading progress. The premise is that singing (while at the same time having a visual display of the words in the songs) can be a very useful instructional tool to teach reading to beginning readers. The process involves learning o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 5 publications
3
12
0
2
Order By: Relevance
“…The authors (Iwasaki et al, 2013) described student growth over an entire school year and the results revealed that all but one student made at least one year's growth in reading; however, several students exceeded the average reading growth for the year. While the results were impressive, the data were limited to the Developmental Reading Assessment (Beaver, 1997) levels, and did not include the specifics on reading fluency measures.…”
mentioning
confidence: 96%
See 1 more Smart Citation
“…The authors (Iwasaki et al, 2013) described student growth over an entire school year and the results revealed that all but one student made at least one year's growth in reading; however, several students exceeded the average reading growth for the year. While the results were impressive, the data were limited to the Developmental Reading Assessment (Beaver, 1997) levels, and did not include the specifics on reading fluency measures.…”
mentioning
confidence: 96%
“…Although Iwasaki et al (2013) implemented the musical activity comprehensively (i.e., word study, writing, comprehension), the method could be modified to target reading fluency. Singing while reading already possesses two important elements of a fluency building activity-repeated readings and an opportunity to perform.…”
mentioning
confidence: 99%
“…Iwasaki et al () described another performance method where students learned one or two songs each week while reading the words as they sang. After implementing this karaoke‐type classroom activity for an entire school year, all but one student made at least one year's growth in reading and several students exceeded the expectation for reading growth.…”
mentioning
confidence: 99%
“…Este juego bidireccional en el ámbito de los sonidos del lenguaje a través de la canción pueden ser una puerta de entrada al desarrollo de la conciencia fonética, fonémica y fonológica. La naturaleza de la rima de la mayoría de las letras de las canciones también proporciona a los profesores excelentes recursos para la enseñanza de las familias de palabras en relación con los distintos campos semánticos trabajados en el aula (Iwasaki et al 2013) La canción en la obra de Roald Dahl La forma canción, como el propio Dahl reconoce (Sturrock, 2010), es un elemento que utiliza de manera casi sistemática a lo largo de toda su obra como recurso, a modo de aria narrativa, para la caracterización de roles y personajes. Sirva como ejemplo una de las obras más paradigmáticas de autor, Charlie y la Fábrica de Chocolate; en ella Dahl incluye cinco canciones escritas con la intención de intensificar ciertos aspectos, acciones o acontecimientos ocurridos, o por suceder en la narración, y que constituyen un vehículo para la apelación directa al lector.…”
Section: Issn 2171-9624unclassified